Admission Patterns and Outcome in a Pediatric Intensive Care Unit at Tobruk Hospital - Gresh, Hawa; Othman, Rehab (Al-Mukhtar Journal of Sciences, 2018)
This study aims to describe the admission pattern and outcome of patients in the pediatric intensive care unit (PICU) at Tobruk medical center. We have retrospectively reviewed medical files of PICU over the period from January to December of 2016 for children aged from 1month-15 years. A total of 1026 children were admitted to PICU at Tobruk medical center. Of the total, 55% were males and 44.9% were females with male to female ratio of 1.2: 1. Age distribution showed that 64% were infants (1month -1 year). Majority of admission during cold months (December, January, and February) had the highest admission rate. Central nervous system and respiratory system diseases (23%, 12%) respectively were the most diseases requiring PICU admission. Congenital heart diseases 10/26 (38.4%) was the most common cause of total death. 668(65%) patients improved and were discharged from ICU, and 201 (19.5%) were transferred to pediatric ward for further management and discharged in satisfactory condition. 99 (9.6%) patients left against medical advice, and 32 (3%) patients transferred to more specified hospital and 26 patient died (2.5%). The observed difference in the mortality was with the respect to age, length of stay, and the involved systems. Neurological system remains a major cause for admission in ICU mainly for febrile convulsion and was associated with considerable morbidity and mortality. Respiratory system was the second cause mainly for pneumonia, and CHD was the major cause of death. The results concluded that epidemiologic analysis of the pattern of patients admitted to our PICU showed different etiologies for admission